Child-Friendly Mosque: A Study of the Strategic Role of the Baiturrahman Mosque in Empowering the Ummah in the City of Banda Aceh - Marpuah, Marpuah; Atieqoh, Siti; Siagian, Salamah (The Sunan Ampel Review of Political and Social Sciences, 2024)
As the center of community development, the existence of mosques is now faced with various changes and challenges that continue to roll in the community. The issue of globalization and information is a phenomenon that cannot be ignored. The increasingly dominant information sector in people's lives will certainly have many implications, including opportunities and challenges for Muslims in socializing and actualizing in the wider community. The central role of the mosque is increasingly required to be able to accommodate and keep up with all developments that occur in society. To realize the role of the mosque as the center of activity. This research focuses on the strategic role of the Baiturrahman Mosque in empowering the ummah in the city of Banda Aceh, with a special emphasis on the concept of "Child Friendly Mosque." As one of the oldest and most iconic mosques in Aceh, the Baiturrahman Mosque serves not only as a place of worship, but also as a center of social, educational, and community empowerment activities. This research aims to explore how Baiturrahman Mosque facilitates programs that support children's development, and to examine the impact of these initiatives on local community empowerment. The research method used was a qualitative descriptive approach, with a case study approach. Data was collected through in-depth interviews, participatory observation, and document analysis. The results of the study are expected to provide insights into the important role of mosques in shaping the character of the younger generation and strengthening communities through inclusive and sustainable programs